2021
DOI: 10.1017/s1049023x21000844
|View full text |Cite
|
Sign up to set email alerts
|

The Psychosocial Impact of Compounding Humanitarian Crises Caused by War and COVID-19 Informing Future Disaster Response

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has caused the greatest global loss of life and economic impact due to a respiratory virus since the 1918 influenza pandemic. While health care systems around the world faced the enormous challenges of managing COVID-19 patients, health care workers in the Republic of Armenia were further tasked with caring for the surge of casualties from a concurrent, large-scale war. These compounding events put a much greater strain on the health care system, creating a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Accounts from health care workers describe the emotional demands of caring for very ill patients with COVID-19 while fearing becoming infected themselves, having to treat patients even when being personally infected, and working shifts that were nearly 24 hours long with little sleep during the pandemic. 6 In the present study, 77.1% of participants reported not having access to the PPE they felt they needed to treat patients. With the outbreak of war, providers found themselves treating gruesome war injuries, transporting war casualties up to six hours, and https://doi.org/10.1017/S1049023X22001522 Published online by Cambridge University Press additionally tending to wounded or deceased colleagues as ambulances, health care workers, and medical facilities became the target of enemy drone attacks and artillery.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Accounts from health care workers describe the emotional demands of caring for very ill patients with COVID-19 while fearing becoming infected themselves, having to treat patients even when being personally infected, and working shifts that were nearly 24 hours long with little sleep during the pandemic. 6 In the present study, 77.1% of participants reported not having access to the PPE they felt they needed to treat patients. With the outbreak of war, providers found themselves treating gruesome war injuries, transporting war casualties up to six hours, and https://doi.org/10.1017/S1049023X22001522 Published online by Cambridge University Press additionally tending to wounded or deceased colleagues as ambulances, health care workers, and medical facilities became the target of enemy drone attacks and artillery.…”
Section: Discussionmentioning
confidence: 56%
“…Prior to the COVID-19 pandemic, 40% of EMS responses were "double calls," in which a second ambulance is dispatched after the first team completes its evaluation for the purpose of providing specialty treatment such as cardiac, neurologic, or psychiatric care, 5 thereby ideally matching a provider with pertinent training to the patient's pathology. However, in the case of this dual disaster response, during which there was a physician shortage forcing EMS physicians to work long hours without substantial backup help, 6 providers of all sorts of specialty backgrounds were responding to potentially critically ill patients often outside of their scope of expertise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this study are consistent with earlier studies, which found that the fear that people experienced during the pandemic affects their perceptions of risk and the older CALD people may be prone to perceive a greater risk on the basis of a sense of uncertainty, vulnerability, and lack of control, 9 , 10 or fear of unknown. 6 It provides important understanding of the compounding nature of intersecting vulnerabilities, such as age, gender or culture, in the context of COVID-19, and contributes to global perspectives on the psychosocial impact of COVID-19 where there may also be social vulnerability, 56 humanitarian crisis, 57 or extreme weather events. 58 …”
Section: Discussionmentioning
confidence: 99%